The Role of the Tumor Vasculature in the Host Immune Response: Implications for Therapeutic Strategies Targeting the Tumor Microenvironment - Hendry, Shona A.; Farnsworth, Rae H.; Solomon, Benjamin; Achen, Marc G.; Stacker, Steven A.; Fox, Stephen B. (Frontiers in Immunology, 2016)
Recently developed cancer immunotherapy approaches including immune checkpoint inhibitors and chimeric antigen receptor (CAR) T cell transfer are showing promising results both in trials and in clinical practice. These approaches reflect increasing recognition of the crucial role of the tumor microenvironment in cancer development and progression. Cancer cells do not act alone, but develop a complex relationship with the environment in which they reside. The host immune response to tumors is critical to the success of immunotherapy; however the determinants of this response are incompletely understood. The immune cell infiltrate in tumors varies widely in density, composition, and clinical significance. The tumor vasculature is a key component of the microenvironment that can influence tumor behavior and treatment response, and can be targeted through the use of anti-angiogenic drugs. Blood vascular and lymphatic endothelial cells have important roles in the trafficking of immune cells and controlling the microenvironment, and modulate the immune response. Improving access to the tumor through vascular alteration with anti-angiogenic drugs may prove an effective combinatorial strategy with immunotherapy approaches, and might be applicable to many tumor types. In this review we briefly discuss the host’s immune response to cancer and the treatment strategies utilizing this response, before focusing on the pathological features of tumor blood and lymphatic vessels and the contribution these might make to tumor immune evasion.